MECHANISMS OF THE KIDNEY DAMAGE IN CASE OF OBESITY AND METABOLIC SYNDROME (REVIEW) - Юлия Николаевна Шишкова; Наталья Николаевна Миняйлова; Юрий Иванович Ровда; Любовь Михайловна Казакова (The Publishing House Medicine and Enlightenment, 2018)
Obesity and metabolic syndrome influence the functions of body's systems, provoke a progressive kidney damage and are development factors of chronic nephron number in reference to body mass. A long-term impact of these factors leads to glomerulosclerosis and chronic renal failure development. The detection of kidney disease. The kidney damage in case of obesity is related to the adipokine production failure, activation of the renin-angiotensin system, chronic inflammation, dyslipidemia, violation of kidney hemodynamics, reduction of early signs and biomarkers of the kidney damage at children is a necessary condition for prevention of the renal failure development.